Microbiological study of neonatal sepsis in a tertiary care hospital of western Uttar Pradesh, India - Garg, Amit; Kumar, Deepesh; Kumar, Sujeet (International Journal of Research in Medical Sciences, 2017)
Background: Neonatal sepsis is a clinical syndrome characterized by systemic signs of infection and accompanied by bacteraemia in the first month of life. Neonatal sepsis is among the three most common illnesses among newborns, and second most common cause of neonatal mortality especially among preterm and low birth weight babies. Aim of the study was to identify the common bacterial pathogens associated with neonatal sepsis and their antibiotic susceptibility pattern. Methods: Total 120 blood samples collected aseptically (from January 2015 to April 2015) and cultured in automated machine Versa TREKTM automated microbial detection system. Significant bacterial colonies are seen on streak lines which were observed by their diameter, opaqueness, flatness, regular or irregular margins etc. Any growth was subjected for identification by appropriate biochemical tests. Antibiotic susceptibility testing was done. Results: Out of one hundred twenty (120) samples, eighty (66.67%) samples were found positive for bacterial infection. In which 22 (27.50%) E.coli, 14 (17.50%) Klebsiella pneumonia, 10 (12.50%) pseudomonas, 17 (21.25%) Staphylococcus aureus, 6 (7.50%) coagulase negative staphylococci (CoNS) and 11(13.75%) Enterococcous sp. was identified. Conclusions: The blood culture positivity rate was 66.67%. E. coli, Klebsiella spp, and Staphylococcus aureus was the commonest agent.